The effect of monetary policy on the balance of payments vulnerability in the CEMAC zone - Liwoh, Nongoh Gilbert; Boniface, Epo Ngah; Atanga, Mary Bi Suh (International Journal of Publication and Social Studies, 2024)
The main objective of this study was to examine the effects of monetary policy on the vulnerability of balance of payments in the CEMAC zone. Data for this study was obtained from the World Development Indicators (WDI) and World Governance Indicators (WGI) databases which are World Bank databases and also from IMF country reports spanning from 1996 to 2020. The ARIMA model used to generate the balance of payments vulnerability while the Panel Tobit model was used to estimate the model. The results revealed that monetary policy has a negative and significant effect on balance of payments vulnerability in the CEMAC zone. This finding was consistent with the results of the correlated panels corrected standard errors (PCSES) regression model for robustness which also revealed that monetary policy has a negative and significant effect on the balance of payments vulnerability in the CEMAC zone. It was recommended that the monetary authority should make policies that would give viable balance of payments for the CEMAC countries, such as increasing the country’s international competitiveness; that is, investing on projects that are productive in order to increase productivity. Secondly, we also recommended that more efforts be put in order abandon the Franc de la Communauté Financière Africaine (Franc CFA) and move to a currency that will provide the region with some level of autonomy in the financial sector.